GENDER EQUALITY AND GENDER EQUITY: AN OVERVIEW OF NIGERIA - Damilola Elizabeth oluwakemmy (International Journal of Research Science and Management, 2016)
The major aim of this paper is to ascertain the level, differential, and prediction of gender equality and gender equity in Nigeria and the specific objectives are to Identify the reasons for gender equality; Identify the reasons for gender equity; Assess the Strategies to promoting gender equality between women and men; Assess the Strategies to promoting gender equity in Nigeria; Examine the attributes of gender equality; and Examine the attributes of gender equality. Women, have become major factors in economic development and are increasingly at the core of a country’s competitive advantage in the global economy. Secondary data from Nigeria Demographic Survey, Nigeria Demographic and Education Survey, National bureau of statistics and National Population Commission (NPC) data were used. The result showed that majority of Nigeria women had no education while little percentage of men had no education. The result showed that Nigerian women face a lot of violence due to gender disparity and that there is gender inequality neither is there gender equity in Nigeria and also that gender equity is more realistic than gender equality. Nigeria should thereby work towards gender equity and not equality.